2013
DOI: 10.1038/ismej.2013.124
|View full text |Cite
|
Sign up to set email alerts
|

Shotgun metagenomics indicates novel family A DNA polymerases predominate within marine virioplankton

Abstract: Virioplankton have a significant role in marine ecosystems, yet we know little of the predominant biological characteristics of aquatic viruses that influence the flow of nutrients and energy through microbial communities. Family A DNA polymerases, critical to DNA replication and repair in prokaryotes, are found in many tailed bacteriophages. The essential role of DNA polymerase in viral replication makes it a useful target for connecting viral diversity with an important biological feature of viruses. Capturi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
62
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(65 citation statements)
references
References 65 publications
(87 reference statements)
3
62
0
Order By: Relevance
“…Instead, virus-focused metagenomics studies either concentrate virus-genomes via their virions or enrich for double-stranded RNA that is a broadly shared feature of virus replication. The virus-enriched nucleic acids are then sequenced by shotgun metagenomics methods (Bibby 2013) for the detection of viruses in environmental material, including marine water (Schmidt et al 2014), fresh water (Mohiuddin & Schellhorn 2015), soil (Ballaud et al 2016), crop plants (Aw et al 2016), native plants and weed plant species (Blouin et al 2016). We remain unable to recommend a single molecular approach to comprehensively target all of the diversity of viral material for metabarcoding studies in an unbiased manner, i.e.…”
Section: Recommendationmentioning
confidence: 99%
“…Instead, virus-focused metagenomics studies either concentrate virus-genomes via their virions or enrich for double-stranded RNA that is a broadly shared feature of virus replication. The virus-enriched nucleic acids are then sequenced by shotgun metagenomics methods (Bibby 2013) for the detection of viruses in environmental material, including marine water (Schmidt et al 2014), fresh water (Mohiuddin & Schellhorn 2015), soil (Ballaud et al 2016), crop plants (Aw et al 2016), native plants and weed plant species (Blouin et al 2016). We remain unable to recommend a single molecular approach to comprehensively target all of the diversity of viral material for metabarcoding studies in an unbiased manner, i.e.…”
Section: Recommendationmentioning
confidence: 99%
“…PUP clade was identified by Breitbart et al (2004), Env clade 1-3 were identified by Labonté et al (2009). Env-4 was identified by Schmidt et al (2014). Env 5 is a new environmental clade that includes cyanophage S-EIV1.…”
Section: S-eiv1-like Viruses In Naturementioning
confidence: 99%
“…Phylogenetic analysis of DNApolA with known phages, metagenomic sequences and amplicons (Breitbart et al, 2004;Labonté et al, 2009;Schmidt et al, 2014) reveals that S-EIV1 along with environmental sequences forms a previously unrecognized evolutionary group of DNApolA sequences (Figure 4). Further evidence for S-EIV1-like phages in aquatic systems was obtained from the recruitment of reads from environmental viral metagenomic data (Figures 6a and b).…”
Section: Dnapol (Orf52) (Supplementarymentioning
confidence: 99%
“…The scale bar represents the number of amino acid substitutions per residue. Huang et al, 2010;Schmidt et al, 2014). Phylogenetic analysis was conducted with 52 different polA amino acid sequences from this study and close relatives retrieved from GenBank ( Figure 3).…”
Section: Diversity Of Cyanopodoviruses As Determined By the Pola Genementioning
confidence: 99%